Documentation and communication in relation with the phytogenetical resources]. - Astorga D, C.; Seidewitz, L. (Centro Agronómico Tropical de Investigación y Enseñanza, Turrialba (Costa Rica)., 2014)
También en microficha *IICA, Turrialba (Costa Rica).